Influence of the solution pH on the morphological, structural and electrical properties of Bi3.50La0.50Ti3O12 thin films obtained by the polymeric precursor method - Simoes, A. Z.; Ries, A.; Moura, F.; Riccardi, C. S.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2005)
Lanthanum-doped Bi4Ti3O12 thin films (BLT) were deposited on Pt/Ti/SiO2/Si substrates using a polymeric precursor solution. The spin-coated films were specular, crack-free and crystalline after annealing at 700 degrees C for 2 h. Crystallinity and morphological evaluation were examined by X ray diffraction (YRD) and atomic force microscopy (AFM). The stability of the formed complex is of extreme importance for the formation of the perovskite phase. Films obtained from acid pH solution present elongated grains around 200 ran in size, whereas films obtained from basic solution present a dense microstructure with spherical grains (100 nm). The dielectric and ferroelectric properties of the BLT films are strongly affected by the solution pH. The hysteresis loops are fully saturated with a remnant polarization and coercive voltage of P-r=20.2 mu C/cm(2) and V-c = 1.35 V and P-r= 15 mu C/cm(2) and V-c = 1.69 V for the films obtained from basic and acid solutions, respectively. (C) 2005 Elsevier B.V. All rights reserved.
Keywords: crystal structure; dielectrics; ferroelectrics; thin films